2022
DOI: 10.1101/2022.06.22.497281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The DEAD-box RNA helicase Dhx15 controls glycolysis and arbovirus replication in Aedes aegypti mosquito cells

Abstract: Aedes aegypti mosquitoes are responsible for the transmission of arthropod-borne (arbo)viruses including dengue and chikungunya virus (CHIKV), but in contrast to human hosts, arbovirus infected mosquitoes are able to efficiently control virus replication to sub-pathological levels. Yet, our knowledge about the molecular interactions of arboviruses with their mosquito hosts is largely incomplete. Here, we aimed to identify and characterize novel host genes that control arbovirus replication in Aedes mosquitoes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…We observed major transcriptional changes at 8 hpi and 48 hpi, which we termed the early and late responses to CHIKV infection, respectively. The late response was more pronounced, with eight upregulated and 51 downregulated genes (Figure 1A), and KEGG pathway analysis suggested that downregulated DEgenes were mainly involved in glycolysis, which we have reported before 35 . In contrast, the early response was modest, with two downregulated and 19 upregulated genes, which were enriched for genes encoding HSP20-like chaperones (Figure 1A).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…We observed major transcriptional changes at 8 hpi and 48 hpi, which we termed the early and late responses to CHIKV infection, respectively. The late response was more pronounced, with eight upregulated and 51 downregulated genes (Figure 1A), and KEGG pathway analysis suggested that downregulated DEgenes were mainly involved in glycolysis, which we have reported before 35 . In contrast, the early response was modest, with two downregulated and 19 upregulated genes, which were enriched for genes encoding HSP20-like chaperones (Figure 1A).…”
Section: Resultssupporting
confidence: 69%
“…For RNA sequencing in Aag2 cells, control dsRNA (dsLuc) treated cells were infected with CHIKV at a MOI of 5. The double stranded RNA treatment was included in the procedure to allow a better comparison of the 4 hpi and 8 hpi samples to the 48 hpi datasets that was generated in parallel for a previously published study 35 .…”
Section: Rna-seq Library Preparation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…From the mass spectrometry data, we identified one peptide unique to Loqs-PA in NS1 immunoprecipitations, whereas other peptides were shared between the three isoforms ( [23], and AAEL004859 which was shown to have a strong antiviral effect on DENV [38]. Notably, this analysis confirmed the interaction of Loqs with DENV non-structural proteins NS1, NS3 and NS5, enriched by 4.9-, 6.1-and 10.7-fold, respectively.…”
Section: Loqs Is a Flavivirus Proviral Factor In Ae Aegyptimentioning
confidence: 58%
“…In other model systems, transcription factors such as A-MYB and Ci are important for piRNA cluster transcription (Goriaux et al ., 2014; Li et al, 2013). We also tested the H3K36me3 writer, Setd2 (Sun et al, 2005), due to the observed readthrough transcription that was marked by rather a strong continuation of H3K36me3 signals (Figures 3A and D); and subsequently, two m 6A writers, Mellt3 and Mellt14, as recent studies suggested H3K36me3 guided the deposition of m 6A at 3’UTRs (Huang et al, 2019a), which may serve as a signal triggering readthrough transcription (C), 16 mRNA 3’end processing genes (D), 18 RNA export genes and confirmation of Nxf1 knockdown (dsNxf1) with another set of dsRNA (lower panel) (E), 26 general RNA processing genes (Halbach et al ., 2020) and 29 RNA helicase genes (Machado et al, 2022) (F).…”
Section: Extended Data Figures and Tablesmentioning
confidence: 99%